Organofluorine chemistry : synthesis and applications - Reddy, Prakash (Elsevier, 2020)
Organofluorine Chemistry: Synthesis and Applications gives a comprehensive outlook on modern synthetic methodologies for organofluorine compounds. It illustrates chemical, biochemical, and materials applications of fluorine-containing compounds, including synthesis and applications of small molecule compounds in drug discovery, positron emission tomography, and fluorinated polymers in solar cells. This book is of use to scientists working in the interdisciplinary areas, such as chemical, biochemical, and biomedical engineering, as well as those involved in materials science and medicinal chemistry. It is also a useful reference for researchers and graduate students interested in organofluorine chemistry. Provides modern synthetic methods and reactions of organofluorine compounds Incorporates the synthesis and chemical, biochemical and biomedical applications of fluorine-containing compounds, nanomaterials, PET imaging agents, pharmaceuticals, and polymeric materials Features emerging "hot" topics, such as late-stage fluorinations and drug discovery